The science of empire : scientific knowledge, civilization, and colonial rule in India - Baber, Zaheer (Albany : State University of New York Press, 1996)
In The Science of Empire, Zaheer Baber analyzes the social context of the origins and development of science and technology in India from antiquity through colonialism to the modern period. The focus is on the two-way interaction between science and society: how specific social and cultural factors led to the emergence of specific scientific/technological knowledge systems and institutions that transformed the very social conditions that produced them. A key feature is the author's analysis of the role of precolonial trading circuits and other institutional factors in transmitting scientific and technological knowledge from India to other civilizational complexes. A significant portion represents an analysis of the role of modern science and technology in the consolidation of the British empire in India.
1. Introduction -- 2. Science, Technology, and Social Structure in Ancient India -- 3. Science, Technology, and Society in Medieval India -- 4. The Origins of British Colonial Rule -- 5. Scientific Solutions for Colonial Problems -- 6. Science, Technology and Colonial Power -- 7. Conclusions: Science, Technology and Ecological Limits.
Includes bibliographical references (p. [257]-287) and index.
Keywords: Science -- Social aspects -- India -- History; Technology -- Social aspects -- India -- History; India -- History -- British occupation, 1765-1947.